2022
DOI: 10.3389/fpsyg.2022.891566
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Presence vs. Student Perceived Preparedness for Testing in Higher Education Online English Courses During a Global Pandemic? Challenges, Tensions, and Opportunities

Abstract: In the context of a global pandemic that started in 2020, the Chilean higher education institution Universidad Andrés Bello (UNAB) faced the challenge of giving continuity to its already established blended program for English courses while also starting the implementation of a high-stakes certification assessment for its students using the Test of English for International Communication (TOEIC) Bridge. This study sought to evaluate how much of a mediating factor online teaching presence could be in the contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Disengaged, absentee students (Usher et al, 2021), serious levels of attrition (World Bank, 2020), frustrated and unprepared teachers (Charbonneau-Gowdy et al, 2021;Moralista & Oducado, 2020), macro and meso level administrators scrambling and often at a loss to find answers (Morales et al, 2022) compromised assessments and results (Guangul et al, 2020), technical infrastructural issues (Chisadza et al, 2021) are just some of the most notable problems reported. A World Bank report (see Figure 2), issued in the early stages of the pandemic, revealed the far-reaching costs of the unpreparedness of systems to move online-especially the costs to individual societies as a whole, in terms of human capital and equality.…”
Section: An Overview Of Covid-19-based Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Disengaged, absentee students (Usher et al, 2021), serious levels of attrition (World Bank, 2020), frustrated and unprepared teachers (Charbonneau-Gowdy et al, 2021;Moralista & Oducado, 2020), macro and meso level administrators scrambling and often at a loss to find answers (Morales et al, 2022) compromised assessments and results (Guangul et al, 2020), technical infrastructural issues (Chisadza et al, 2021) are just some of the most notable problems reported. A World Bank report (see Figure 2), issued in the early stages of the pandemic, revealed the far-reaching costs of the unpreparedness of systems to move online-especially the costs to individual societies as a whole, in terms of human capital and equality.…”
Section: An Overview Of Covid-19-based Literaturementioning
confidence: 99%
“…While the emphasis at the institution has been on research for over a decade and its institutional policies aim clearly at idealistic goals for quality education, it can be said that despite these efforts, in terms of teaching, the institution has struggled to adopt 21 st century goals and current learning practices across the board in its classrooms and to incorporate technology as an integral part of its programming (Morales et al, 2022).…”
Section: Context and Participantsmentioning
confidence: 99%
“…However, it is said that although practising is essential for creating effective presentations because the presenters (students) are able to improve their presentations, the lecturers and students are disturbed with the number of assessment practices apart from the obligations to other work commitments and official responsibilities (Hanifa & Yusra, 2018). Another study by Mohd Radzuan and Kaur (2011) and Morales et al (2022) supported the argument that the lack of preparedness for the assessments will make the students fail to complete their project successfully.…”
Section: Introductionmentioning
confidence: 99%